THE APPLICATION OF GAMES IN DEVELOPING STUDENTS’ SPEAKING SKILL IN EFL CLASSROOM - Ana Kuliahana (ISTIQRA: Jurnal Hasil Penelitian, 2021)
This research was aimed at developing students speaking skill in EFL classroom through the application of games. The research was designed in the form of Classroom Action Research. It was conducted in two cycles and six meetings. Each cycle consisted of plan, implementation, observation and Reflection. The researcher employed observation checklist, field notes, questionnaire, and test to collect the data. The main criterion of success of this research was that the students’ scores on speaking test should achieve the score of 70; and it must be achieved by 75% of the total number of students. The second criterion was that the teacher’s classroom performance should meet “Success” category. The results of the first speaking test showed that from 24 students in class TBI-1 FTIK IAIN Palu, there were 15 students got the scores of 70 or higher. It was equal to 62.5 %. In cycle 2, the total number of students who got the scores of 70 or higher was 21. It was equal to 87.5 %. The result of this research indicated that the application of games was effective to develop the students’ speaking skills. Keywords: